Dating sexual violence: Relevance of prevention - Caridade, Sónia (2008)
This article presents a systematic review of the current body of literature about sexual violence in dating relationships. This review was based on the articles published during the 1985-2006 period in the databases PsyARTICLES, PsyINFO1887, Sociology: A SAGE Full-Text Collection, EBSCO-HOST: Research Databases e IBSS – International Bibliography of the Social Science, as well as on the analysis of books published during the same period. Based on this revision, this text presents the prevalence rates of sexual violence between dating partners and analyses its risk factors. The prevention culture on this topic is also described, exploring the different kinds of preventive actions and the efficacy. In conclusion, reflections about the limitations of the prevention program conduced in this area are made and some suggestions for future actions with youth populations are presented. DOI: http://dx.doi.org/10.17575/rpsicol.v22i1.339